Orality and Literacy. Unmarked and Marked Elements in Verbal Comunication - Nagy, Gregory (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
Introductory comments marking the occasion of an international conference on orality and literacy, University of Wrocław 2019.12.04–06
Keywords: oral theory